(untitled) (Raíces: Revista de Ciencias Sociales y Políticas, 2018)
The study of borders has had a great boom especially in recent years in Latin America and the Caribbean. In the case of Central America, the borders have been considered as zones of conflict between the countries that share them. Historically, these have not received attention from the State, remaining forgotten and attended only when new border or territorial conflicts appear. In other diverse fields of social and human sciences, the notion of frontier is taken into account in a broader sense and is not systematically translated into the boundaries between states. The term is used to express a separation between cultural groups (linguistic, religious border) and is associated with a confused, imprecise, mobile contact. The border has the ability to directly affect the configuration of the towns, cities and towns that develop along it. However, this capacity for influence is divergent and discontinuous due to various factors of a historical, geographical, socioeconomic and political nature. The present investigation has the purpose of producing a work that deals with the study of the locality of Cárdenas and its border regions, understanding them as those spaces of transcendence for the development of these and of Nicaragua, from an integrating and multidisciplinary perspective.